PROJECT MANAGEMENT IN PROFESSIONAL EDUCATION: PROBLEMS, SOLUTIONS AND PROSPECTS - Ibragimova Madina Mamasolievna (American Journals, 2024)
This article examines the current state of project management education in Uzbekistan's professional education system. It identifies key challenges including outdated curricula, lack of qualified instructors, and limited hands-on learning opportunities. Potential solutions are explored, such as modernizing course content, providing instructor training and certification, and incorporating more practical projects. The future prospects of project management education in Uzbekistan are discussed, emphasizing the need to align programs with global standards and best practices to produce competitive professionals. Through literature review and analysis of two professional education institutions, this article provides insights to advance project management education in Uzbekistan.
Keywords: Project management, professional education, Uzbekistan, curriculum development, globalization